2018
DOI: 10.1111/famp.12374
|View full text |Cite
|
Sign up to set email alerts
|

The Added Value of Studying Embodied Responses in Couple Therapy Research: A Case Study

Abstract: This article reports on the added value of embodied responses identified through sympathetic nervous system (SNS) activity in couple therapy research. It focuses on moments of change and the timing of therapeutic interventions or therapeutic moves in a couple therapy session. The data for this single-case study comprise couple therapy process videotapes recorded in a multi-camera setting, and measurements of participants' SNS activity. The voluntary participants were a marital couple in their late thirties and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
21
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 17 publications
(22 citation statements)
references
References 33 publications
0
21
0
1
Order By: Relevance
“…In our subjectively meaningful social learning sessions, we were also interested in detecting critical moments of change that had made the selected episodes B1 and B2 personally meaningful for Lisa's learning within the Leadership Coaching Program. In line with the analysis of Laitila et al (2018), we expected that those values of EDA which represented rare (p>.05) high peaks would reveal exceptionally high unconscious emotional arousal of the subject, and thus point to critical moments of learning. In the analyses of Lisa's EDA, we compared the numbers of statistically significant high peaks between episodes of about the same length.…”
Section: Analysis Of the Datamentioning
confidence: 62%
See 2 more Smart Citations
“…In our subjectively meaningful social learning sessions, we were also interested in detecting critical moments of change that had made the selected episodes B1 and B2 personally meaningful for Lisa's learning within the Leadership Coaching Program. In line with the analysis of Laitila et al (2018), we expected that those values of EDA which represented rare (p>.05) high peaks would reveal exceptionally high unconscious emotional arousal of the subject, and thus point to critical moments of learning. In the analyses of Lisa's EDA, we compared the numbers of statistically significant high peaks between episodes of about the same length.…”
Section: Analysis Of the Datamentioning
confidence: 62%
“…It can be measured by well-established and non-intrusive techniques that provide unique information on emotional arousal, increased cognitive work load, and taskengagement. Overall, the higher the conductance level rises, the more elevated the subject's emotional arousal becomes (Huhtamäki et al, 2017;Laitila et al, 2018). It has been suggested that if EDA is a good predictor of cognitive load, task difficulty, and task engagement, it might also be used for predicting boredom, disengagement, and frustration in learning (Azevedo et al, 2013(Azevedo et al, , 2016.…”
Section: The Strengths and Limitations Of Self-reporting Physiologicmentioning
confidence: 99%
See 1 more Smart Citation
“…Moving beyond the conflicts about epistemology that can be a block to bringing science to practice, these postmodern clinicians and researchers have begun to look at research methodologies from psychotherapy research that are most compatible with their world view applied to couple and family therapy. Thus, we have seen use of patient-focused research assessing self-reported progress (Sparks & Duncan, 2018), various methods of linguistic analysis (Ong, Barnes, & Buus, 2019;Sutherland, LaMarre, Rice, Hardt, & Le Couteur, 2017) and research centered on physiological and interpersonal processes (Laitila et al, 2019;Seikkula, Karvonen, Kykyri, Penttonen, & Nyman-Salonen, 2018). Most of all, several of these researchers have tapped into the long-standing tradition of psychotherapy process research to look at the what is happening in the therapy process, especially in terms of client and therapist experience (Laitila et al, 2019;Lambert, 2016).…”
mentioning
confidence: 99%
“…Thus, we have seen use of patient-focused research assessing self-reported progress (Sparks & Duncan, 2018), various methods of linguistic analysis (Ong, Barnes, & Buus, 2019;Sutherland, LaMarre, Rice, Hardt, & Le Couteur, 2017) and research centered on physiological and interpersonal processes (Laitila et al, 2019;Seikkula, Karvonen, Kykyri, Penttonen, & Nyman-Salonen, 2018). Most of all, several of these researchers have tapped into the long-standing tradition of psychotherapy process research to look at the what is happening in the therapy process, especially in terms of client and therapist experience (Laitila et al, 2019;Lambert, 2016). Strikingly, the use of qualitative methods, with their ability to examine the nuances of responses and their intrinsic acknowledgment of the possibility of bias by the investigator, has been easier to incorporate than quantitative measures (Hooghe, Rosenblatt, & Rober, 2017;Kao & Caldwell, 2017).…”
mentioning
confidence: 99%